THE CONCEPT AND FUNCTIONS OF EUPHEMISMS IN LANGUAGE (Web of Teachers: Inderscience Research, 2025)
Euphemisms play an important role in social communication, helping to reduce emotional stress and create comfortable conditions for interaction in society.